Hak Memperoleh Keadilan Dalam Sistem Peradilan Di Indonesia - Aniek Periani; rusito rusito (Faculty of Law, Universitas Wijayakusuma, 2022)
Abstract Constitutionally, the Indonesian state has guaranteed, respected, respected and protected human rights. Before the amendments were made, the 1945 Constitution could be said to have not explicitly stated the guarantee of human rights. However, after the amendment of the 1945 Constitution, especially the second amendment in 2000, the provisions regarding human rights in the 1945 Constitution have undergone fundamental changes. This amendment to the 1945 Constitution contains human rights material as regulated in Article 28A paragraph (1) to Article 28j paragraph (2). By using normative juridical research methods, this study aims to determine the efforts that must be made to obtain justice in the justice system in Indonesia. The justice to be enforced in the constitutional state of the Republic of Indonesia is justice that contains the values of the Pancasila philosophy, the 1945 Constitution and the values contained in other legislation, whose values are aspirational with the values and sense of community justice. Meanwhile, the way to enforce law and justice is carried out in accordance with the implementation procedure based on the principle of presumption of innocence and other principles determined by the Criminal Procedure Code. Keywords: Justice, Human Rights, Criminal Procedure Code Abstrak Secara konstitusional negara Indonesia telah menjamin, menghormati, menjunjung tinggi dan melindungi Hak Asasi Manusia. Sebelum dilakukan perubahan, UUD 1945 dapat dikatakan tidak mencatumkan secara tegas mengenai jaminan Hak Asasi Manusia. Tetapi setelah UUD 1945 diamandemen, terutama amandemen kedua tahun 2000, ketentuan mengenai HAM dalam UUD 1945 telah mengalami perubahan yang mendasar. UUD 1945 perubahan ini telah memuat materi HAM yang diatur dalam pasal 28A ayat (1) sampai dengan pasal 28j ayat (2). Dengan menggunakan metode penelitian yuridis normatif, penelitian ini bertujuan untuk mengetahui upaya yang harus dilakukan untuk memperoleh keadilan dalam sistem peradilan di Indonesia. Keadilan yang hendak ditegakkan di negara hukum Republik Indonesia adalah keadilan yang mengandung nilai-nilai falsafah Pancasila, UUD 1945 serta nilai-nilai yang terdapat dalam perundang-undangan yang lain, yang nilai-nilainya aspiratif dengan nilai dan rasa keadilan masyarakat. Sedangkan cara menegakkan hukum dan keadilan dilakukan sesuai dengan tata pelaksanaan yang berpedoman kepada asas praduga tidak bersalah dan asas-asas lain yang ditentukan KUHAP. Kata Kunci : Keadilan, Hak Asasi Manusia, Hukum Acara Pidana